Circulating metabolites associated with brain MRI markers of Alzheimer's disease: Neuroimaging / imaging and genetics. (7th December 2020) - Wang, Ruiqi; Satizabal, Claudia L; Beiser, Alexa S; Vasan, Ramachandran S; DeCarli, Charles; Gerszten, Robert Edgardo; Yang, Qiong; Seshadri, Sudha
Abstract: Background: Prior research has identified metabolites associated with general cognitive function and Alzheimer's Disease (AD). However, more research is needed to identify additional metabolites related to AD endophenotypes to better understand the earliest pathological processes. We aimed to identify metabolites associated with brain MRI markers of AD, including total brain volume, lateral ventricular volume, and hippocampal volume in the Framingham Heart Study. Method: About 2, 145 participants from the Framingham Heart Study Offspring and Third‐Generation cohorts were used in this project. We used linear mixed effect models to assess the association between metabolites and MRI phenotypes. Brain MRI measures were introduced as the percentage of total intracranial volume to correct for head size. Our primary model was adjusted for age, sex, BMI, and use of lipid‐lowering medications. In secondary analyses, we ran the same model stratifying for APOE4 status subgroups (e4 carriers vs. non‐carriers). Multiple testing corrected significance levels was determined as P < 2.09 × 10 ‐4 after considering inter‐correlation of the metabolites. Finally metabolite set enrichment analysis (MSEA) was carried out to identify biologically meaningful patterns that are significantly enriched in the top associated metabolites. Result: We found that higher levels of cotinine, fumarate‐malate‐valine and lactate were associated with lower total brain volumes (P < 8.13 × 10 ‐5 ). In subgroup analyses, we observed that higher levels of anthranilate were related to lower brain volumes in APOE‐e4 carriers. Further, only in APOE‐e4 non‐carriers, higher phosphatidylcholine (32:1) levels were related to lower brain volumes (P < 1.52 × 10 ‐4 ) and higher levels of urate were related to lower hippocampal volume (P < 1.11 × 10 ‐4 ). Valine, leucine and isoleucine biosynthesis, and aminoacyl‐tRNA biosynthesis are significantly overrepresented for hippocampal volume in APOE‐e4 non‐carriers. Conclusion: Several metabolites were associated with total brain and hippocampal volumes. Remarkably, some of these have been previously related to cognitive function and AD, adding to the consistency of our findings and highlighting the power of endophenotype research. Expansion to include additional brain MRI markers and replication in other neuroCHARGE cohorts, a large international consortium, are currently underway.